1995
DOI: 10.1002/hep.1840210125
|View full text |Cite
|
Sign up to set email alerts
|

The role of sodium in the uptake of ursodeoxycholic acid in isolated hamster hepatocytes

Abstract: The uptake of ursodeoxycholic acid (UDCA) was studied in isolated hamster hepatocytes. The uptake was rapid and linear up to 60 seconds for each concentration studied. When the uptake rate was plotted against UDCA concentration, the curve was nonlinear, indicating both saturable and nonsaturable uptake mechanisms. The nonsaturable process had a diffusion constant of 0.01 nmol.s-1.g of cell.mumol/L-1. The saturable component was characterized by a maximum rate of uptake (Vmax) of 5.68 nmol.s-1.g of cell-1 and a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
6
0

Year Published

1997
1997
2020
2020

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 52 publications
1
6
0
Order By: Relevance
“…Regarding the hepatic uptake of UDCA, it has been reported that the contributions of the Na + -dependent and -independent pathways to its hepatic uptake were almost identical in isolated hamster hepatocytes, which is consistent with our results . On the other hand, we did not see any significant uptake of UDCA via OATP1B1 and OATP1B3, which we expected to work as high-affinity Na + -independent transport systems.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Regarding the hepatic uptake of UDCA, it has been reported that the contributions of the Na + -dependent and -independent pathways to its hepatic uptake were almost identical in isolated hamster hepatocytes, which is consistent with our results . On the other hand, we did not see any significant uptake of UDCA via OATP1B1 and OATP1B3, which we expected to work as high-affinity Na + -independent transport systems.…”
Section: Discussionsupporting
confidence: 92%
“…Regarding the hepatic uptake of UDCA, it has been reported that the contributions of the Na + -dependent and -independent pathways to its hepatic uptake were almost identical in isolated hamster hepatocytes, which is consistent with our results. 28 On the other hand, we did not see any significant uptake of UDCA via OATP1B1 and OATP1B3, which we expected to work as high-affinity Na + -independent transport systems. Britz et al have reported that Bamet-UD2 (cisplatin conjugated with two molecules of UDCA) can be taken up by OATP1A2 (OATP-A), OATP1B1 (OATP-C), organic cation transporter (OCT) 1, OCT2, and NTCP.…”
Section: Discussionmentioning
confidence: 51%
“…16 Initial rate of bile acid uptake was plotted as a function of the corresponding respective bile acid concentration, and data were analyzed by linear curve fitting. 31 …”
Section: Methodsmentioning
confidence: 99%
“…UDCA is a weak acid (pKa = 5), and poorly water soluble, however, its solubility increases directly to the increase of the solution pH. After orally administrations, UDCA must be solubilized in mixed micelles present in small intestinal content in order to allow absorption [19,20]. During the cholestasis disease, the UDCA bioavailability is limited due to the reduction of endogenous BA micelles in the duodenal lumen.…”
Section: Bile Acid Therapy In Hepatobiliary Disease: Role Of Udcamentioning
confidence: 99%